2013
DOI: 10.4236/ajac.2013.41004
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-sensitive LC Method for the Simultaneous Determination of Paracetamol, Carbamazepine, Losartan and Ciprofloxacin in Bulk Drug, Pharmaceutical Formulation and Human Serum by Programming the Detector

Abstract: An ultra-sensitive LC method for the simultaneous quantitation of paracetamol, carbamazepine, losartan and ciprofloxacin have been developed and validated following the ICH guidelines at isobestic point and by programming the detector at individual wavelength of each component. −1 respectively. Percent recoveries > 98.37% from pharmaceutical formulation and human serum samples and RSD < 2% for inter-day and intra-day assay were obtained. The method was found to be robust and can be successfully applied for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A literature review revealed that different methods have been reported for the determination of CBZ. These include spectrophotometry , photoinduced fluorimetry , voltammetry , high‐performance liquid chromatography , spectrofluorimetry , micellar electrokinetic capillary chromatography , solid‐phase extraction , chemiluminescence , liquid chromatography , ion chromatography and gas chromatographic methods .…”
Section: Introductionmentioning
confidence: 99%
“…A literature review revealed that different methods have been reported for the determination of CBZ. These include spectrophotometry , photoinduced fluorimetry , voltammetry , high‐performance liquid chromatography , spectrofluorimetry , micellar electrokinetic capillary chromatography , solid‐phase extraction , chemiluminescence , liquid chromatography , ion chromatography and gas chromatographic methods .…”
Section: Introductionmentioning
confidence: 99%
“…Lisinopril, captopril [13,14] and metformin [15] have also been simultaneously determined with NSAIDs. Sultana and Arayne et al, have also developed methods for the simultaneous determination of various co-administered drugs as calcium channel blockers with NSAIDS [16,17] and many other drugs [18][19][20][21][22][23] in raw materials, pharmaceutical formulations…”
Section: Enalapril Maleate Is Chemically Described As (S)-1-[n-[1-(etmentioning
confidence: 99%
“…Paracetamol (acetaminophen or N-acetyl-4-aminophenol), is a popular analgesic and antipyretic agent, with the following structural formula 1,2 (Figure 1). 3 , HPLC methods [4][5][6][7][8] , HPLC and UV methods [9][10] , HPTLC methods [11][12][13][14] , LC methods [15][16] , UV-spectrophotometric methods [17][18][19][20][21][22][23][24][25] , amperometric method 26 , fluorimetric method 27 , chemiluminescence method 28 and voltametric methods 29 . These methods are required expensive or sophisticated instruments and not simple for routine analysis.…”
Section: Introductionmentioning
confidence: 99%